2009
DOI: 10.4046/trd.2009.67.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Delftia acidovorans Isolated from the Drainage in an Immunocompetent Patient with Empyema

Abstract: Delftia acidovorans is a gram-negative motile rod found ubiquitously in soil and in water. Confirmed isolation from clinical infections is rare, and has been documented mostly in immunocompromised patients or those with indwelling catheters. A 53-year-old man was referred for the evaluation of a huge mass-like lesion found incidentally by chest X-ray. The lesion occupied more than half of the right lung and was diagnosed as a large loculated pleural effusion by CT scan. Bloody pus was drained through a percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
(9 reference statements)
1
15
0
3
Order By: Relevance
“…There have been reports of relapse peritoneal dialysis-related peritonitis (López-Menchero et al, 1998), urine tract infection (del Mar Ojeda-Vargas et al, 1999, and ocular infections (Brinser and Torczynski, 1977;Lee et al, 2008;Stonecipher et al, 1991) related to this agent. Pulmonary infections attributed to D. acidovorans are rarely reported, e.g., a case of pneumonia in an immunocompromised HIV-positive patient (Franzetti et al, 1992) and a case of chronic empyema in the pleural cavity of an immunocompetent man (Chun et al, 2009). A report of D. acidovorans isolated from intercostal drainage tube tip and repeated samples of endotracheal tube aspirates from an immunocompetent child presenting pulmonary infection and empyema that evolved to death (Khan et al, 2012) underscores the relevance of this pathogen from respiratory tract specimens.…”
Section: Introductionmentioning
confidence: 95%
“…There have been reports of relapse peritoneal dialysis-related peritonitis (López-Menchero et al, 1998), urine tract infection (del Mar Ojeda-Vargas et al, 1999, and ocular infections (Brinser and Torczynski, 1977;Lee et al, 2008;Stonecipher et al, 1991) related to this agent. Pulmonary infections attributed to D. acidovorans are rarely reported, e.g., a case of pneumonia in an immunocompromised HIV-positive patient (Franzetti et al, 1992) and a case of chronic empyema in the pleural cavity of an immunocompetent man (Chun et al, 2009). A report of D. acidovorans isolated from intercostal drainage tube tip and repeated samples of endotracheal tube aspirates from an immunocompetent child presenting pulmonary infection and empyema that evolved to death (Khan et al, 2012) underscores the relevance of this pathogen from respiratory tract specimens.…”
Section: Introductionmentioning
confidence: 95%
“…Case reports revealed that all were resistant to gentamicin, and some were resistant to all aminoglycosides. They are generally susceptible to broad-spectrum cephalosporins, piperacillin, aztreonam, carbapenems, quinolones, and trimethoprim-sulfamethoxazole (1,2,3,4,7,8,10,12,17) (Table 2). D. acidovorans has been reported to have ␤-lactamase in two resistant laboratory mutant strains and inducible ␤-lactamase production in one resistant clinical strain (15).…”
Section: Acidovorans Was Formerly Called Comamonas Acidovoransmentioning
confidence: 99%
“…Delftia acidovorans infections have been reported from cases of endocarditis, ocular infections, acute suppurative otitis media, bacteremia, urinary tract infections, intravascular catheter related infections and empyema [2,[5][6][7][8] . Serious infections have been reported from immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%